ON THE ISSUE OF FORMATION OF COMMEMORATIVE CULTURE OF THE KYRGYZ (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The article analyzes the essence of the formation of commemorative culture of theKyrgyz, which is still a little-studied phenomenon in science. The research task was an attempt todetermine the trajectory of commemorative practice, which has acquired particular significance inthe era of globalization. As today it is difficult to find a common understanding of the essence ofhistorical memory as a form of new thinking, a new worldview in the culture of the Kyrgyz people.This scientific article interprets its own emphasis in understanding the formation of acommemorative culture based on the educational and pedagogic potential of the nation. The mainattention is paid to the characteristics of commemoration from the position of other researchers, inparticular, defining this phenomenon as relevant in the education and formation of value systemsof a modern person. In conclusion, the need to form a common vision of commemorative culturein the realities of the 21st century is traced.
Keywords: commemoration, commemorative culture, commemorative practice, globalization, historical memory, value, representation, society, memorial, personality, commemoration, ritual.